Potentially Toxic Elements in Xiphias gladius from Mediterranean Sea and risks related to human consumption. (October 2020) - Di Bella, Giuseppa; Bua, Giuseppe Daniel; Fede, Maria Rita; Mottese, Antonio Francesco; Potortì, Angela Giorgia; Cicero, Nicola; Benameur, Qada; Dugo, Giacomo; Lo Turco, Vincenzo
Abstract: Swordfish is a widely consumed fish worldwide. The aim of this work was to evaluate levels of As, Zn, Mn, Fe, Cu, Al, Cr, Ni, Se, Cd, Pd and Hg in 28 samples of swordfish muscles, coming from zone of Food and Agriculture Organization (FAO) namely 37.1 and 37.2, in order to assess potential public health risks. 100% of the samples had Cd levels not detectable, 32.14% of samples exceeded European maximum limits set for Hg. Health risk assessment showed a not dangerous condition for Al (0.65% of Tolerable Weekly Intake), Ni (0.27% of Tolerable Daily Intake) and Pb (0.68% of Provisional Tolerable Weekly Intake), but very hazardous states for Hg (159.69% of Tolerable Weekly Intake) and As (1099.45% for minimum value of Benchmark Dose Limit). Target Hazard Quotient (THQ) showed dangerous values only for As and Hg. Analytical data of the present study suggest a swordfish prudent consumption. Graphical abstract: Unlabelled Image Highlights: 28 samples of swordfish muscles were analyzed for inorganic contents by ICP-MS. Concentrations of 12 elements were used for health assessment. Analytical data of the present study suggest a swordfish prudent consumption.